Fresno Merced Counties Legal Services Halloween Party at Cindy Calvert's Home - Watkins, Howard::::::::: (1981)
Christine Watkins, Janie Munoz holding Michelob bottle of beer, Cindy Calvert as Catwoman drinking can of Tab